Pembelajaran Berdiferensiasi: Solusi Tepat untuk Meningkatkan Kemampuan Berpikir Kritis Mahasiswa PGSD dalam Mata Kuliah Konsep Dasar IPA - Lisanun Thoyibah Yusuf; Agus Basuki; Azzumardin Syaidi; Fatia Rosyida (Postgraduate, University of Mataram, 2025)
This research aims to determine the effect of differentiated learning on the critical thinking skills of PGSD students in the basic IPA concepts course. The approach used in this research is quantitative, with a quasi-experimental design. The research was conducted on first-semester students at Yogyakarta State University, specifically in class A as the experimental class with 26 people and class B as the control class with 30 people. The results of the paired sample t-test for critical thinking skills between the pretest and post-test in the control class are 8.744 > 1.697 (t-table N=30) and in the experimental class are 33.303 > 1.706 (t-table N=26). In each class, the significance value is 0.001. If compared to the required value for a significance level of 0.05, the calculated significance is less than 0.05, it is stated that there is a positive influence. The findings indicate a positive and significant impact of differentiated learning on enhancing students' critical thinking skills in the basic IPA concepts course. These results indicate that educators need to consider integrating differentiated learning into their teaching strategies to improve the quality of education.